(untitled) (Journal of Asian Geography, 2025)
Disasters have numerous effects on children as one of the vulnerable groups in society. Increasing teachers' knowledge and awareness about Disaster Risk Reduction (DRR) can improve overall disaster resilience in the community. Teachers not only educate school children but also play an important role in shaping school policies and practices related to safety and emergency preparedness. Therefore, this study is exploring the introduction of the importance of DRR education to trainee teachers and evaluating the knowledge of trainee teachers on DRR education. This study utilised a quantitative approach to explore the knowledge of trainee teachers. A sample of indigenous trainee teachers from the Teacher’s Training Institute was taken as respondents. Pre- and post-questionnaires were distributed to the participants in the form of a capacity-building workshop with a total of 46 participants, aged between 18 and 24, engaged in the workshop. Analysis of pre- and post-workshop questionnaires revealed initial uncertainty among trainee teachers about their knowledge of DRR, with a significant change to increased confidence after the workshop. After the workshop, there was a significant increase in the identification of various hazards specific to Malaysia, reflecting increased awareness and understanding. Trainee teachers expressed strong support for integrating hazard education into the school curriculum, highlighting its importance for future generations. Overall, the finding suggests the importance of educating both school students and teachers about DRR to increase community resilience.